Assessment of Smallholder Fish Farming Enterprise in Argungu Local Government Kebbi State - Danmaigoro, Aliyu; Adamu Jega, Abdussalam; Usman Hassan , Shehu (Indonesian Journal of Advanced Research, 2024)
This study aimed to assess the engagement and interest of rural people in fisheries activities in Argungu Local Government Area of Kebbi State. One hundred and fifty (150) questionnaires were randomly distributed in the three villages. The questionnaires consisted of socioeconomic Characteristics as well as the current engagement of the rural people in fisheries activities and their interest in fish farming. The data obtained from the questionnaires was analyzed using descriptive statistics. Results indicate that the majority (73.3%) of these fish farmers are male, compared to (26.7%) who are female. A large proportion of fish farmers have attained primary education (30.7%). Regarding marital status and income levels, (66%) of the fish farmers are married and (68%) of the fish farmers earn less than 10,000 Naira monthly. The results on engagement and interest of smallholder farmers in fish farming enterprises show that (52.7%) of the fish farmers are actively engaged in fish farming. Fish farming enterprises reveal that smoking is the most commonly used method, with (53.2%) of the respondents favoring it. The most prevalent constraints in fish farming enterprise indicate that (58%), is the poor marketing system and poor storage facilities, which affects (56.7%) of the smallholder fish farmers. Based on this, it is recommended that there is a need to assist in setting up small-scale fish farming projects in rural areas with proper monitoring and supervision and Small-scale fish farming policies and practices to significantly improve food security, rural incomes and sustainable aquaculture development.